SIMULASI HIDROLOGI SISTEM DRAINASE KAWASAN JATI KOTA PADANG MENGGUNAKAN HEC-HMS - Fransiska, Yolla; Sari, Putri Kumala (Jurnal Ilmiah Poli Rekayasa, 2025)
The Jati Area in Padang City is one of the urban regions affected by flooding and waterlogging, particularly during the rainy season. The flooding issue in this area is not only caused by the insufficient capacity of the drainage channels but also by the lack of understanding regarding the hydrological characteristics of the region. Therefore, a hydrologically based modeling approach is essential to analyze and predict the response of the catchment area to rainfall, surface runoff discharge, and the effectiveness of the existing drainage system. In this study, the author models the drainage system in the Jati area using the HEC-HMS program, with the aim of obtaining the peak discharge value during extreme rainfall events and determining the timing of the maximum discharge. HEC-HMS is a widely used software for hydrologic modeling, particularly for simulating the runoff process from a watershed area. The research consists of three main stages: data collection, data processing, and drawing conclusions from the results. Based on the simulation results of the hydrologic modeling analysis of the drainage network in the Jati area, it was found that the channels at certain nodes are unable to accommodate the design discharge load, resulting in flooding due to the insufficient capacity of those channels. The results of this study can be used by policymakers for the redesign of drainage infrastructure, such as modifying the channel dimensions from a base width of 6.5 m, 6.8 m, and 6.8 m at reach 9, reach 10, and reach 11 respectively, to 8.5 m based on the peak discharge from the simulation results, which is 37.5 m³/s.